Agroforestry practices in the Ethiopian highlands - Berhe, Kahsay; Mohamed-Saleem, M.A. (Ethiopian Agricultural Research Organization, 2001)
The first part of this paper looks into what agroforestry is; the need for agroforestry and its benefits. Then the paper outlines and discusses the basic systems in agroforestry including simulataneous agroforestry systems; linear agroforestry systems; alley cropping (hedgerow intercropping); sequential agroforestry systems; shifting cultivation (slash and burn or swidden); improved tree fallow; and Taungya. It also examines briefly other agroforestry practices including aquaforestry and entomoforestry. The paper ends with highlights on agroforestry practices for soil conservation, and watershed management